A Pattern for Concept Identification from English Translated Quran - Rohana, Ismail; Nurazzah, Abd Rahman; Zainab, Abu Bakar (2017)
Ontology development is time consuming and tedious task. The task can be minimized by automatic or semi-automatic ontology development. This minimizing task is a field of ontology learning. Ontology learning will be able to extract ontological elements to form ontology. Concept identifying is one of the important activities in ontology learning. Various methods can be used to find concepts. Thus, this experiment used the n-grams and JAPE pattern in identifying concepts. As the term Allah occurs very frequent in English translated Quran, this experiment considers the word surrounding the term Allah to find other related concepts. It is important because the occurrences produced the term Allah as a concept in ontology but at the same time ignore other related terms to term Allah. The strength connection between words surrounding term Allah has been analysed. Results show the significant terms related to term Allah can be extracted. Later, the term can be used as concepts in ontology.